Drosophila citron kinase is required for the final steps of cytokinesis. - Naim, V.; Imarisio, S.; Di Cunto, F.; Gatti, M.; Bonaccorsi, S. (Molecular Biology of the Cell, 2004)
The mechanisms underlying completion of cytokinesis are still poorly understood. Here, we show that the Drosophila orthologue of mammalian Citron kinases is essential for the final events of the cytokinetic process. Flies bearing mutations in the Drosophila citron kinase (dck) gene were defective in both neuroblast and spermatocyte cytokinesis. In both cell types, early cytokinetic events such as central spindle assembly and contractile ring formation were completely normal. Moreover, cytokinetic rings constricted normally, leading to complete furrow ingression. However late telophases of both cell types displayed persistent midbodies associated with disorganized F actin and anillin structures. Similar defects were observed in dck RNA interference (RNAi) telophases, which, in addition to abnormal F actin and anillin rings, also displayed aberrant membrane protrusions at the cleavage site. Together, these results indicate that mutations in the dck gene result in morphologically abnormal intercellular bridges and in delayed resolution of these structures, suggesting that the wild-type function of dck is required for abscission at the end of cytokinesis. The phenotype of Dck-depleted cells is different from those observed in most Drosophila cytokinesis mutants but extraordinarily similar to that caused by anillin RNAi, suggesting that Dck and anillin are in the same pathway for completion of cytokinesis.